Afrotropical culicoides : biosystematics of the Imicola group, subgenus Avaritia (Diptera: ceratopogonidae) : with special reference to the epidemiology of African horsesickness - Meiswinkel, Rudolf (University of Pretoria, 2022)
Dissertation (MSc (Agric))--University of Pretoria, 1995.